Endometrial carcinoma in women aged 65 and older. Clinical and pathological analysis - Korczyński, Jerzy; Gottwald, Leszek; Góra, Ewa; Bieńkiewicz, Andrzej (Menopause Review/Przegląd Menopauzalny, 2006)
Study objective: A retrospective analysis of 49 patients with endometrial carcinoma undergoing radical hysterectomy was done. A review of pathology findings and clinical data was performed. Materials and methods: 21 cases of hysterectomy in women aged 65 or older were analyzed and compared to a group of 28 younger patients. Cancer morphology, myometrium infiltration, nodal metastases and presence of endometrial polyps were discussed. Results: Endometrioid carcinoma was noticed in 82.1% of cases of hysterectomy in younger women. Myometrial layer infiltration of more than 50% thickness was noticed in 52.4% of patients aged 65 and older. Histologically, 13 (62%) older patients had carcinoma involving the cervix. 8 patients had pelvic node metastases. Of the 49 patients, 18 (36.7%) had endometrial polyps. No differences were observed in frequency of cancer lesions in the polyps group of patients. Conclusions: Endometrioid carcinoma as well as G1 grade of cancer are typical in women aged 65 or younger. Cervix involvement is significant in older women. No differences in additional pathology of the genital tract were found between the two groups of patients with endometrial cancer.